Animals as a Stereotyping and Characterising Element in Slovenian Name-Callings - Babič, Saša (Traditiones, 2024)
The article discusses deeply rooted linguistic comparisons as stereotypical images in the form of name-callings. A very common element of these comparisons are animals as living beings with their own characteristics, living in a common environment: A human characteristic is compared to a prescribed, but not necessarily intrinsic, characteristic of a particular animal. The characteristics ascribed to animals are socially stereotyped and disseminated as generalised images using a metaphorical language that form so-called collective symbols.